EDUCATIONAL ENVIRONMENT FOR MARKETERS IN THE DIGITAL WORLD - Marchenko, Svitlana; Dymenko, Ruslan; Gonca Telli, Yamamoto (Socio-economic relations in the digital society, 2023)
The educational environment for marketers in the digital world involves a number of key aspects that are important to consider, namely: digital technologies, analytics and measurement, strategic thinking, creativity and innovation, communication skills, branding and positioning, project management skills, continuous learning and adaptation. The digital world presents many opportunities for marketers, but it also presents challenges. The educational environment of marketers in the digital world involves constant updating of knowledge and skills in the use of new digital tools and marketing strategies, a deep understanding of the digital audience, its behaviour and expectations, as well as the ability to adapt to rapid changes in technologies and platforms. Marketers in the digital world must be prepared to constantly learn, adapt and develop their skills to operate effectively in the fast-changing digital environment and achieve marketing goals. The purpose of the article is to generalize the forms, goals, and opportunities of educational activities of marketers in the digital world with an in-depth justification of each direction. It was determined that the digital educational environment has a number of advantages and disadvantages, which must be taken into account for the purpose of correct application. However, it is important not to forget about the need to ensure interpersonal relationships and social interaction to ensure the full development of the applicants of the "Marketing" speciality.
Keywords: formal and informal education of marketers; digital educational environment tools; digital technologies